Case report of old anterior dislocation of the shoulder joint and review of the literature - Guo, Weiming; Hui, Ming; Yang, Yuan; Wan, Teng; Zeng, Guang-Gui; Huang, Peiguan; Wang, Xiaoxu; Qiu, Mingjun (Frontiers in Surgery, 2022)
Background Dislocation of the shoulder joint is the most common type of joint dislocation. It is rare to be in a persistent dislocation that has not been reset. Successful arthroscopic treatment of the obsolete shoulder is relatively uncommon. Case report We report a rare case of persistent anterior dislocation of the old shoulder joint in a 30-year-old female patient. The patient underwent an emergency shoulder dislocation at a local hospital after a traumatic injury and re-dislocated persistently after surgery. 26 days later, she was admitted to our department for treatment, mainly because of joint deformity and limitation of motion. We adopted arthroscopic release and repositioning surgery. The patient was followed up for 1 year after surgery. Functional recovery was satisfactory. Conclusion The state of obsolete shoulder dislocation rarely occurs after shoulder dislocation and the prognosis of the patient is good after complete arthroscopic release and repositioning. It provides a reference for clinical arthroscopic treatment of old shoulder dislocations.